Radio-frequency (RF) sensing for deep awareness of human physical status - part II - Quek, Yan Zhuang (Nanyang Technological University, 2022)
With our society becoming more reliant on technology, it is undeniable that we have seen more areas of our lives being improved with the aid of technologies. Especially in the area of healthcare and lifestyle, more health-related devices such as health-trackers, oximeters and health related applications have appeared exponentially in the consumer market.